Development of Transient Differential Model of Bell-Delaware Method with A Case Study of Water/TiO2 Nanofluid (Journal of Advanced Thermal Science Research, 2015)
Heat exchangers are equipments designed for efficient and economic thermal energy transfer between chemical process flows, being widely applied in chemical plants, petrochemical, refinery and power plants. This work aims the development of a rigorous transient model for a 1-2 shell-and-tube of heat exchangers with fractionated baffles, implementing Bell-Delaware method to determine the thermal and fluid dynamics parameters like heat transfer coefficients and pressure drop. For this, Bell-Delaware method has been utilized to the shell-side, considering several types of baffle leaks and its configuration, bypass effect in tube bundles, different input and output distances of baffles, laminar flow, temperature gradient and viscosity variation near the tubes walls. Nanofluid physical properties were locally evaluated by adapted prediction equations available in databases and literature. The case study simulations were performed using the Python computer program and its modules, to determine temperature and physical properties and profiles of TiO2 nanofluid through the tube, considering a one-dimensional variation, and showing the model applicability for dimensioning and analysis of shell-and-tube 1-2 exchangers.
Keywords: Bell-Delaware; nanofluid; Python; rigorous model